11.4k views
24 votes
Step by step please.

Step by step please.-example-1
User Fadel
by
5.2k points

1 Answer

9 votes

Ok so the general form of a circle is given by;

(x-a)²+(y-b)²=r²

where a and b are the coordinates of the center

and r is the radius of the circle

For this case we know that the center is (5,-7)

So the general equation of the circle would be;


(x - 5) {}^(2) + (y - ( - 7)) {}^(2) = r {}^(2)


(x - 5 {}^(2) + (y + 7) {}^(2) = r {}^(2)

Since we know that (-3,-1) is a point on that circle, we can say that it satisfies the equation of the circle;


( - 3 - 5) {}^(2) + ( - 1 + 7) {}^(2) = r {}^(2)


r {}^(2) = ( - 8) {}^(2) + ( 6) {}^(2)


r {}^(2) = 64 + 36 = 100

So now,


(x - 5) {}^(2) + ( {y + 7)}^(2) = 100

User Jensgram
by
5.4k points